PENGARUH JOB INSECURITY DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN RUMAH SAKIT UMUM MITRA SEJATI MEDAN - Mayora, Lingga Ivan; Sihombing, Marlon (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to determine the effect of job insecurity and workload on employee turnover intention at Mitra Sejati Hospital Medan. Turnover intention will be tested partially and simultaneously on job insecurity and workload. A total of 86 workers were used as samples for this quantitative study. Purposive sampling was used for data collection. A straight distribution questionnaire using a Likert scale was used to compile the data. Multiple linear regression analysis with the help of SPSS version 25 is used to test the validity, reliability, and test the classical assumptions and test the hypothesis. Based on the results of the study that the job insecurity has a partial effect on turnover intention, this is evidenced by the value of t-statistic 5.526 > t-table 1.663. While the workload variable also partially affects turnover intention, this is evidenced by the value of t-statistic 4.579 > t-table 1.663. Based on simultaneous testing that the job insecurity and workload variables have a simultaneous effect on turnover intention with F-statistic 69.467 > F-table 3.11 and an R value of 0.791 and the Adjusted R Square in the study is 61.7% while the remaining 38,3% is influenced by other factors not examined in this study.